Communication Patterns and Work Culture Across Professional Hofstede’s Perspective - Mustika Pertiwi (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2026)
Communication patterns and work culture are important elements in organizations because they influence how individuals interact, coordinate work, and interpret power relations and work values. This study aims to analyze communication patterns and work culture across professions in Indonesia using Hofstede's six dimensions of culture as a framework for analysis at the professional level. Unlike previous studies, which were generally comparative between countries, this study positions Hofstede's theory in the context of a single national culture to examine cultural differences in work culture between professions.This study uses a qualitative approach through in-depth interviews with four informants representing the professions of teacher, journalist, banker, and government employee. The data were analyzed through thematic categorization based on Hofstede's six cultural dimensions, namely power distance, individualism-collectivism, masculinity-femininity, uncertainty avoidance, long-term orientation, and indulgence-restraint. The results show that the four professions have relatively homogeneous cultural tendencies in the dimensions of collectivism, femininity, and long-term orientation, reflecting the strong influence of Indonesian national culture. The novelty of this research lies in the contextual reading of Hofstede's theory at the professional level, which shows that professional and institutional culture plays an important mediating role in organizational communication and work practices.